Lifetime spirometry patterns of obstruction and restriction, and their risk factors and outcomes: a prospective cohort study. Issue 3 (March 2023) - Dharmage, Shyamali C; Bui, Dinh S; Walters, Eugene H; Lowe, Adrian J; Thompson, Bruce; Bowatte, Gayan; Thomas, Paul; Garcia-Aymerich, Judith; Jarvis, Debbie; Hamilton, Garun S; Johns, David P; Frith, Peter; et al.
Summary: Background: Interest in lifetime lung function trajectories has increased in the context of emerging evidence that chronic obstructive pulmonary disease (COPD) can arise from multiple disadvantaged lung function pathways, including those that stem from poor lung function in childhood. To our knowledge, no previous study has investigated both obstructive and restrictive lifetime patterns concurrently, while accounting for potential overlaps between them. We aimed to investigate lifetime trajectories of the FEV1 /forced vital capacity (FVC) ratio, FVC, and their combinations, relate these combined trajectory groups to static lung volume and gas transfer measurements, and investigate both risk factors for and consequences of these combined trajectory groups. Methods: Using z scores from spirometry measured at ages 7, 13, 18, 45, 50, and 53 years in the Tasmanian Longitudinal Health Study (n=2422), we identified six FEV1 /FVC ratio trajectories and five FVC trajectories via group-based trajectory modelling. Based on whether trajectories of the FEV1 /FVC ratio and FVC were low (ie, low from childhood or adulthood) or normal, four patterns of lifetime spirometry obstruction or restriction were identified and compared against static lung volumes and gas transfer. Childhood and adulthood characteristics and morbidities of these patterns were investigated. Findings: The prevalence of the four lifetime spirometry patterns was as follows: low FEV1 /FVC ratio only, labelled as obstructive-only, 25·8%; low FVC only, labelled as restrictive-only, 10·5%; both low FEV1 /FVC ratio and low FVC, labelled as mixed, 3·5%; and neither low FEV1 /FVC ratio nor low FVC, labelled as reference, 60·2%. The prevalence of COPD at age 53 years was highest in the mixed pattern (31 [37%] of 84 individuals) followed by the obstructive-only pattern (135 [22%] of 626 individuals). Individuals with the mixed pattern also had the highest prevalence of parental asthma, childhood respiratory illnesses, adult asthma, and depression. Individuals with the restrictive-only pattern had lower total lung capacity and residual volume, and had the highest prevalence of childhood underweight, adult obesity, diabetes, cardiovascular conditions, hypertension, and obstructive sleep apnoea. Interpretation: To our knowledge, this is the first study to characterise lifetime phenotypes of obstruction and restriction simultaneously using objective data-driven techniques and unique life course spirometry measures of FEV1 /FVC ratio and FVC from childhood to middle age. Mixed and obstructive-only patterns indicate those who might benefit from early COPD interventions. Those with the restrictive-only pattern had evidence of true lung restriction and were at increased risk of multimorbidity by middle age. Funding: National Health and Medical Research Council of Australia, The University of Melbourne, Clifford Craig Medical Research Trust of Tasmania, The Victorian, Queensland & Tasmanian Asthma Foundations, The Royal Hobart Hospital, Helen MacPherson Smith Trust, and GlaxoSmithKline.